Labor and the Social Being: reflections regarding the Lukacsian ontology and its occurrence in the Professional Ethical-Political Project / Trabalho e Ser Social: reflexões sobre a ontologia Lukacsiana e sua incidência no Projeto Ético-Político... - Júnior, Reginaldo Pereira; Lara, Ricardo (Textos & Contextos (Porto Alegre), 2015)
ABSTRACT – This article, originating from the reflections of the "Labor and Social Issues in Latin America" Studies and Research Nucleus at the Social Services Graduate program at Federal University of Santa Catarina (UFSC), intends to point out elements for understanding the profession as it is today, in addition to conducting an analysis of the labor category in Marx and Lukács and its relation to Social Services as salaried profession inserted in the social and technical division of labor, which contributes to the process of (re)producing the logic of capital. Determined by the capitalist sociability, it is important to note that Social Services are in a collision path with the interests of capital because, due to the nature and determinations of capital, the "contradiction" element is self-determining. The profession, which is complementary to the collective interests of the working class, seeks to use a professional project, connected to a class project, to adhere to collective values that meet the concrete needs which emanate from the working class towards a radical construction of a new sociability. Keywords – Labor. Ontology. Social Services. Ethical-Political Project. RESUMO – Este artigo, originário das reflexões do Núcleo de Estudos e Pesquisas “Trabalho e Questão Social na América Latina”, do departamento de pós-graduação em Serviço Social da Universidade Federal de Santa Catarina (UFSC), tem a intenção de apontar elementos para compreensão da profissão na atualidade, além de realizar uma análise sobre a categoria “trabalho” em Marx e Lukács e sua relação com o Serviço Social como profissão assalariada inserida na divisão social e técnica do trabalho, que contribui com o processo de (re)produção da lógica do capital. Determinada pela sociabilidade capitalista, é importante assinalar que o Serviço Social situa-se numa zona de colisão com os interesses do capital, pois pela sua natureza e as determinações do capital o elemento “contradição” se autodetermina. Sendo tributária dos interesses coletivos advindos da classe trabalhadora, a profissão busca, por meio de um projeto profissional vinculado a um projeto de classe, a adesão a valores coletivos que atendam às necessidades concretas emanadas da classe trabalhadora na direção da construção radical de uma nova sociabilidade. Palavras-chave – Trabalho. Ontologia. Serviço Social. Projeto Ético-Político.